1998
DOI: 10.1136/bjsm.32.4.309
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic strength testing does not predict hamstring injury in Australian Rules footballers.

Abstract: Objective-To determine the relation of hamstring and quadriceps muscle strength and imbalance to hamstring injury using a prospective observational cohort study Method-A total of 102 senior male Australian Rules footballers aged 22.2 (3.6) years were tested at the start of a football season. Maximum voluntary concentric and eccentric torque of the hamstring and quadriceps muscles of both legs was assessed using a Kin-Com isokinetic dynamometer at angular velocities of 60 and 180 degrees/second. Twelve (11.8%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
281
8
17

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(320 citation statements)
references
References 14 publications
(11 reference statements)
14
281
8
17
Order By: Relevance
“…H:Q ratio increased from 69.6±11.8% at 60°/s to 76.7±13.5% at 180°/s and these results showed similarity with the values at 60 °/s (69%) and 180 °/s (73%) angular velocities reported by Bennell, et al (28)., Rosene et al evaluated the conventional H:Q ratios in intercollegiate athletes (soccer and volleyball) and they found that H:Q ratio was higher at 180 °/s (58.6 %) than at 120°/s (53.6 %) and at 60 °/s (49.8 %) angular velocities in female athletes (17). However, the ratios in their study were lower than the ratios in this study.…”
Section: Angular Velocitysupporting
confidence: 79%
See 1 more Smart Citation
“…H:Q ratio increased from 69.6±11.8% at 60°/s to 76.7±13.5% at 180°/s and these results showed similarity with the values at 60 °/s (69%) and 180 °/s (73%) angular velocities reported by Bennell, et al (28)., Rosene et al evaluated the conventional H:Q ratios in intercollegiate athletes (soccer and volleyball) and they found that H:Q ratio was higher at 180 °/s (58.6 %) than at 120°/s (53.6 %) and at 60 °/s (49.8 %) angular velocities in female athletes (17). However, the ratios in their study were lower than the ratios in this study.…”
Section: Angular Velocitysupporting
confidence: 79%
“…There was no descriptive data about the subjects' physical characteristics, hamstring and quadriceps peak torques so we could not hypothesize what cause the different outcomes between two studies. The similar finding of the other study reported an increase in the H:Q ratio from 61±14.3% at 60°/s to 62±14.7% at 90°/s in nondisabled, sedentary individuals (28).…”
Section: Angular Velocitysupporting
confidence: 76%
“…Apesar de alguns estudos demonstrarem a ocorrência de assimetrias em atletas de futebol 2,9,11 , outros trabalhos não suportam esses achados 1,10,12 . Considerando as diferenças no gesto esportivo determinadas pelas diversas funções exercidas pelos jogadores, é possível que a presença de assimetria nesses atletas esteja relacionada ao posicionamento em campo.…”
Section: Introductionunclassified
“…However, it seems that fatigue of only one of the limbs alters this common command and dissociating the command for both limbs (1) . In practical terms, training, as well as the familiarization to tasks, may reduce the bilateral strength deficit minimizing the asymmetry, especially at fatiguing conditions, in which the control dissociation may modify the overload between limbs, since tasks which present asymmetry between limbs are more prone to injuries during physical performance (30)(31)(32)(33)(34)(35)(36) .…”
Section: Asymmetryindices (%) Dominantmentioning
confidence: 99%